All-polymer Layer by Layer coating as efficient solution to polyurethane foam flame retardancy. (September 2015) - Carosio, Federico; Negrell-Guirao, Claire; Alongi, Jenny; David, Ghislain; Camino, Giovanni
Graphical abstract: Highlights: An all-polymer Layer by Layer coating has been developed for the protection of polyurethane foams. The coating can conformally coat the complex structure of the open-cell foams. The coating prevented foam collapsing during flammability and cone calorimetry tests. Foam dangerous melt dripping was suppressed after the deposition of only 2 bi-layers. 4 bi-layers reduced the heat release rate by 55%. Abstract: This paper deals with the Layer by Layer assembly of an all-polymer chitosan/poly(allylamine diphosphonate) coating characterized by high efficiency in reducing the flammability of open cell polyurethane foams. The Layer by Layer assembly of the two components yields a supralinear growing coating that can be easily deposited on the complex 3D structure of polyurethane foams while preserving the open cell nature of the substrate. 2 bi-layers (BL) are enough to guarantee the deposition of a continuous thin coating capable of preventing the dangerous melt dripping phenomenon during flammability tests. The very same coating can dramatically reduce the heat release rate under a 35 kW/m 2 heat flux as it can efficiently hinder the foam structural collapsing during combustion. 2 BL coatings achieve a reduction of 48% while 4 BL reaches the maximum reduction of 55%, thus confirming the great efficiency of the coating in reducing the PU flammability at such low deposition steps and coating thicknesses.